Etnopharmacy Study of Medical Plants in Sulawesi - Kauntu, Rafael; Zuhrotun, Ade; Iskandar, Yoppi (Sam Ratulangi University, 2026)
Sulawesi Island, Indonesia, is recognized for its high biodiversity and rich cultural diversity, both of which contribute to the extensive use of medicinal plants in traditional healthcare systems. The increasing global interest in plant-based medicine—driven by the rising prevalence of chronic diseases, antimicrobial resistance, and concerns regarding the adverse effects of synthetic drugs—highlights the importance of documenting regional ethnopharmaceutical knowledge. This study aims to synthesize available literature on medicinal plants traditionally used by communities in Sulawesi. A systematic literature review was conducted using electronic databases, including Google Scholar, PubMed, and Elsevier, covering publications from 2014 to 2025. Articles were screened based on predefined inclusion criteria, resulting in 20 eligible studies. The findings identified 17 plant species used across six provinces, with leaves as the most frequently utilized plant part (64.70%) and decoction as the predominant preparation method (47.05%). Five representative species—Ficus septica, Lansium domesticum, Blumea balsamifera, Cymbopogon citratus, and Piper betle—demonstrate pharmacological potential supported by phytochemical and experimental evidence. Although traditional use aligns with emerging scientific findings, clinical validation and standardization remain limited. These results emphasize the urgency of systematic documentation and rigorous scientific evaluation of medicinal plants in Sulawesi to support biodiversity conservation and future drug discovery initiatives.